Nanometer silane-zirconized composite automobile surface pretreatment liquid and preparation method thereof

By introducing nanoparticles and optimized components into the automotive surface treatment liquid, the nanosilane-zirconization composite pretreatment liquid is formed, which solves the problems of insufficient film thickness and corrosion resistance in traditional technology, and achieves higher adhesion and resistance Corrosion performance meets the high performance requirements of the automotive industry.

CN119144948AInactive Publication Date: 2024-12-17ANGANG STEEL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411210866.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional silane and zirconization pretreatment technologies have problems in automotive surface treatments such as insufficient film thickness and hiding properties, high penetration requirements for electrophoretic paint swimmers, complex treatment processes, and poor corrosion resistance.

Method used

By introducing nanoparticles and optimizing the components and preparation process of the pretreatment liquid, nanosilane-zirconized composite automobile surface pretreatment liquid is used. The nanoparticles are nanosilica and nanozinc oxide, with particle sizes ranging from 30 to 50 nm, combined with γ -Aminopropyltriethoxysilane coupling agent and zirconium salt form a dense mesh structure, enhancing the hardness and corrosion resistance of the coating.

Benefits of technology

It significantly improves the adhesion and corrosion resistance of the pretreatment liquid, meets the requirements of the automotive industry for high-performance surface treatment, and solves the problem of insufficient performance of traditional technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005020285520000061
    Figure BDA0005020285520000061
Patent Text Reader

Abstract

The invention discloses a nano silane-zirconized composite automobile surface pretreatment fluid and a preparation method thereof. The composite automobile surface pretreatment fluid comprises the following components in parts by mass: 1-10 parts of nano particles, 1-10 parts of a silane coupling agent, 1-15 parts of zircon salt, 0.5-5 parts of a surfactant, 0.5-3 parts of a dispersing agent, 1-5 parts of a pH regulator and 50-75 parts of deionized water. According to the method, the nanoparticles are introduced and the components and the preparation process of the pretreatment liquid are optimized, so that good dispersion and compatibility of the nanoparticles in the pretreatment liquid are realized, and the adhesive force and the corrosion resistance of the pretreatment liquid are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of automobile surface treatment, and specifically relates to a nano-silane-zirconium composite automobile surface pre-treatment liquid and a preparation method thereof. Background Art

[0002] With the rapid development of the automobile industry and the continuous advancement of technology, automobile surface treatment technology has received increasing attention. The purpose of automobile surface treatment is to improve the adhesion and corrosion resistance of the coating, thereby extending the service life of the car. Among the traditional automobile surface treatment technologies, silane and zirconization pretreatment technologies are two commonly used methods. Silane coupling agents have excellent adhesion and can form a dense silane film on the metal surface, effectively improving the corrosion resistance and wear resistance of the coating. Zirconium salts can form a stable zirconization film on the metal surface, which also has good corrosion resistance. However, with the continuous improvement of the automobile industry's requirements for automobile surface treatment performance, the single use of silane or zirconization pretreatment technology has problems in automobile corrosion protection, such as insufficient film thickness and hiding power, high requirements for electrophoretic paint penetration, complex treatment process, and poor corrosion resistance.

[0003] In recent years, the rapid development of nanotechnology has brought new breakthroughs in automotive surface treatment technology. Nanoparticles have the characteristics of high specific surface area, high activity, excellent mechanical properties and chemical stability due to their unique size effect and surface effect. Introducing nanoparticles into the automotive surface pretreatment liquid can significantly improve the performance of the pretreatment liquid, making it have better adhesion and corrosion resistance. The application of nanoparticles in automotive surface pretreatment liquid mainly utilizes the high specific surface area and activity of nanoparticles to enhance the interaction between the pretreatment liquid and the metal surface and improve the adhesion of the coating. Summary of the invention

[0004] The present invention achieves good dispersion and compatibility of nanoparticles in the pretreatment liquid by introducing nanoparticles and optimizing the components and preparation process of the pretreatment liquid, and significantly improves the adhesion and corrosion resistance of the pretreatment liquid. The technical solution not only solves the problems existing in the traditional silane and zirconization pretreatment technologies, but also brings new breakthroughs to automobile surface treatment technology through the introduction of nanotechnology.

[0005] In order to achieve the above-mentioned purpose of the invention, the present invention provides a nano-silane-zirconium composite automobile surface pretreatment liquid, which comprises the following components in parts by weight: 1 to 10 parts of nanoparticles, 1 to 10 parts of silane coupling agents, 1 to 15 parts of zirconium salts, 0.5 to 5 parts of surfactants, 0.5 to 3 parts of dispersants, 1 to 5 parts of pH regulators, and 50 to 75 parts of deionized water.

[0006] In the above technical solution, further, the nanoparticles are nano silicon dioxide and nano zinc oxide, and the particle size is 30-50nm. The nano silicon dioxide and nano zinc oxide are added to the dispersion medium anhydrous ethanol in a weight ratio of (2-3):1, and ultrasonic waves are used to disperse them. The ultrasonic frequency is set to 100-300kHz, and the dispersion time is 15-30min. The use of nanoparticles is an important reinforcing component of the treatment liquid. These nanoparticles can form a dense network structure in the coating due to their ultrafine particle size and unique physical and chemical properties, thereby improving the hardness and corrosion resistance of the coating.

[0007] The silane coupling agent is prepared by mixing γ-aminopropyl triethoxysilane (KH-550) and γ-glycidyloxypropyl trimethoxysilane (KH-560) in a weight ratio of (1-2): 1. The silane coupling agent can chemically react with the nanoparticles and the surface of the metal substrate to form a strong chemical bond, thereby enhancing the adhesion between the coating and the substrate.

[0008] The zirconium salt is prepared by mixing zirconium nitrate (Zr(NO3)4) and zirconium chloride (ZrCl4) in a weight ratio of (1-2):2. The zirconium salt is an inorganic crosslinking agent, and the zirconium ions contained in the zirconium salt can form a three-dimensional crosslinking network with the silane coupling agent and nanoparticles to improve the corrosion resistance of the coating. This crosslinking structure can also effectively prevent the coating from cracking, peeling, etc. during use.

[0009] The surfactant is prepared by mixing sodium dodecyl sulfate (SDS), cocamidopropyl betaine (CAPB), sodium fatty alcohol polyoxyethylene ether sulfate (AES), and sodium dodecylbenzene sulfonate (LAS) in a weight ratio of (1-2):1:1:1. The surfactant can reduce the surface tension of the treatment liquid and enhance its wettability and spreadability.

[0010] The dispersant is prepared by mixing sodium polyacrylate (PAAS), polyvinyl pyrrolidone (PVP), and sodium carboxymethyl cellulose (CMC-Na) in a weight ratio of (2-3): 2: 1. The dispersant can ensure that the nanoparticles are evenly dispersed in the pretreatment solution and prevent the nanoparticles from agglomerating.

[0011] The pH regulator is prepared by mixing citric acid, sodium hydroxide (NaOH), and sodium hydrogen phosphate (Na2HPO4) in a weight ratio of (1-2): 1: 1. The pH regulator is used to adjust the pH of the treatment liquid to ensure that it performs optimally under optimal process conditions.

[0012] Deionized water: Using deionized water as a solvent can ensure the stability and compatibility of each component in the treatment solution. Through the dilution and mixing of deionized water, each component can be evenly dispersed in the entire treatment solution to form a uniform and stable system.

[0013] A method for preparing the above-mentioned nano-silane-zirconium composite automobile surface pretreatment liquid, the preparation method comprising the following steps:

[0014] ① Take 30 to 45 parts of deionized water, heat it to 40°C to 50°C, then add the surfactant and continue stirring for 15 to 30 minutes at a stirring speed of 300 to 500 rpm to form a surfactant solution;

[0015] ② Take 5 to 10 parts of deionized water, heat it to 50°C to 60°C, then add the dispersant and continue stirring for 15 to 30 minutes at a stirring speed of 400 to 600 rpm to form a dispersant solution;

[0016] ③ According to the compounding ratio, citric acid, sodium hydroxide and sodium hydrogen phosphate are added to 5-10 parts of deionized water, stirred at a speed of 400-600 rpm for 15-30 minutes to prepare a pH regulator solution;

[0017] ④ Mix zirconium nitrate and zirconium chloride in a weight ratio of (1-2):2 to prepare the required zirconium salt;

[0018] ⑤ Adjust the stirring speed of the high-speed stirrer to 1300-1500 rpm, add the nanoparticles, stir for 15-30 minutes, then add the silane coupling agent and zirconium salt, and continue stirring for 15-30 minutes;

[0019] ⑥ Add the surfactant solution obtained in step ①, the dispersant solution obtained in step ②, the pH regulator solution obtained in step ③, and the remaining deionized water into the high-speed stirrer, control the stirring speed to 2000-3000 rpm, the stirring temperature to 60° C.-75° C., and the stirring time to 45-60 minutes to obtain a nano-silane-zirconium composite automobile surface pretreatment liquid.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention provides a nano-silane-zirconium composite automobile surface pretreatment liquid and a preparation method thereof. The pretreatment liquid has excellent adhesion and corrosion resistance and can meet the high performance requirements of the automobile industry for surface treatment. The technical solution solves the problem of insufficient performance of traditional silane and zirconium pretreatment technologies when used alone, and provides a new technical path for automobile surface pretreatment technology. DETAILED DESCRIPTION

[0022] The present invention is further described below in conjunction with specific examples, but the present invention is not limited in any way. To avoid redundant description, the raw materials in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods unless otherwise specified.

[0023] A nano-silane-zirconium composite automobile surface pretreatment liquid comprises the following components by weight: 1-10 parts of nanoparticles, 1-10 parts of silane coupling agents, 1-15 parts of zirconium salts, 0.5-5 parts of surfactants, 0.5-3 parts of dispersants, 1-5 parts of pH regulators, and 50-75 parts of deionized water.

[0024] Example

[0025] A nano-silane-zirconium composite automobile surface pretreatment liquid, the components and mass contents of the nano-silane-zirconium composite automobile surface pretreatment liquid of Examples 1-10 are shown in Table 1. By introducing nanoparticles and optimizing the components and preparation process of the pretreatment liquid, good dispersion and compatibility of the nanoparticles in the pretreatment liquid are achieved, and the adhesion and corrosion resistance of the pretreatment liquid are improved.

[0026] Table 1 Example 1-10 Components and contents of nano-silane-zirconium composite automobile surface pretreatment liquid

[0027] Components Nanoparticles Silane coupling agent Zirconium salt Surfactants Dispersants pH Adjusters Deionized water Content / portion 1~10 1~10 1~15 0.5~5 0.5~3 1~5 50~75 Example 1 5 5 6 1 0.5 2 60 Example 2 5 4 8 2 1.2 1.5 55 Example 3 6 8 5 1.5 1.5 1 58 Example 4 4 6 9 2.5 1 2 65 Example 5 8 5 12 1.2 2 3 63 Example 6 4 7 10 3 1.5 4 70 Example 7 2 3 12 4 3 2 73 Example 8 6 7 14 3.5 2 3.5 68 Example 9 9 8 11 3 2.5 4.5 72 Example 10 8 7 10 4 3 4 70

[0028] A method for preparing the above-mentioned nano-silane-zirconium composite automobile surface pretreatment liquid, the specific steps are as follows:

[0029] ① According to the mass ratio of the components in the above embodiments, take 30 to 45 parts of deionized water, heat it to 40°C to 50°C, then add the surfactant and continue stirring for 10 minutes at a stirring speed of 500 rpm to form a surfactant solution.

[0030] The surfactant is prepared by mixing sodium lauryl sulfate, cocamidopropyl betaine, sodium fatty alcohol polyoxyethylene ether sulfate and sodium dodecylbenzene sulfonate in a weight ratio of 2:1:1:1, and stirring at a speed of 500 rpm for 15 minutes.

[0031] ② Take 5 to 10 parts of deionized water, heat it to 50°C to 60°C, then add the dispersant and continue stirring for 15 minutes at a stirring speed of 600 rpm to form a dispersant solution.

[0032] The dispersant is prepared by mixing sodium polyacrylate, polyvinyl pyrrolidone and sodium carboxymethyl cellulose in a weight ratio of 3:2:1, and stirring at a stirring speed of 400 rpm for 10 minutes.

[0033] ③ According to the compounding ratio of citric acid: sodium hydroxide: sodium hydrogen phosphate by weight = 2:1:1, take citric acid, sodium hydroxide and sodium hydrogen phosphate and add 5 to 10 parts of deionized water, stir at 600 rpm for 30 minutes to prepare a pH regulator solution.

[0034] ④ Mix zirconium nitrate and zirconium chloride in a weight ratio of 1:2 to obtain the required zirconium salt.

[0035] ⑤ Adjust the stirring speed of the high-speed stirrer to 1500 rpm, add the nanoparticles, stir for 30 minutes, then add the silane coupling agent and zirconium salt, and continue stirring for 15 minutes.

[0036] The nanoparticles are nano silicon dioxide and nano zinc oxide, and the particle size is 50nm. Nano silicon dioxide and nano zinc oxide are added into the dispersion medium anhydrous ethanol at a weight ratio of 2:1, and are dispersed by ultrasonic wave, the ultrasonic wave frequency is set to 300kHz, and the dispersion time is 20 minutes.

[0037] The silane coupling agent is prepared by mixing γ-aminopropyltriethoxysilane KH-550 and γ-glycidyloxypropyltrimethoxysilane KH-560 in a weight ratio of 1:1, and stirring at a stirring speed of 400 rpm for 20 minutes.

[0038] ⑥ Add the surfactant solution obtained in step ①, the dispersant solution obtained in step ②, the pH regulator solution obtained in step ③, and the remaining deionized water into the high-speed stirrer, control the stirring speed to 3000 rpm, the stirring temperature to 60° C. to 75° C., and the stirring time to 60 minutes to obtain a nano-silane-zirconium composite automobile surface pretreatment liquid.

[0039] The nano-silane-zirconium composite automobile surface pretreatment liquid was prepared by adopting the above process flow and according to the components and contents of Examples 1-10 in Table 1; the test pieces were respectively immersed in the nano-silane-zirconium composite automobile surface pretreatment liquid prepared in Examples 1-10, the test pieces were taken out and dried, and the anti-rust performance test was carried out according to SH / T 0533 "Rust Assessment Method for Rust Test Pieces of Anti-Rust Grease". The coating adhesion test was carried out on the surface of the test piece according to GB / T 9286 "Scratching Test of Paint and Varnish Film", and Table 2 shows the implementation technical effects of the products prepared in Examples 1-10.

[0040] Table 2 Implementation effect of embodiments 1-10

[0041]

[0042] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A nano-silane-zirconium composite automobile surface pretreatment liquid, characterized in that: The composite automobile surface pretreatment liquid comprises the following components in parts by weight: 1 to 10 parts of nanoparticles, 1 to 10 parts of silane coupling agents, 1 to 15 parts of zirconium salts, 0.5 to 5 parts of surfactants, 0.5 to 3 parts of dispersants, 1 to 5 parts of pH regulators, and 50 to 75 parts of deionized water.

2. The composite automobile surface pretreatment liquid according to claim 1, characterized in that: The nanoparticles are nano silicon dioxide and nano zinc oxide, and the particle size thereof is 30-50 nm. The nano silicon dioxide and nano zinc oxide are added into the dispersion medium anhydrous ethanol in a weight ratio of (2-3):1, and are dispersed by ultrasonic wave, the ultrasonic wave frequency is set to 100-300 kHz, and the dispersion time is 15-30 minutes.

3. The composite automobile surface pretreatment liquid according to claim 1, characterized in that: The silane coupling agent is prepared by mixing γ-aminopropyltriethoxysilane KH-550 and γ-glycidyloxypropyltrimethoxysilane KH-560 in a weight ratio of (1-2):

1.

4. The composite automobile surface pretreatment liquid according to claim 1, characterized in that: The zirconium salt is prepared by mixing zirconium nitrate and zirconium chloride in a weight ratio of (1-2):

2.

5. The composite automobile surface pretreatment liquid according to claim 1, characterized in that: The surfactant is prepared by mixing sodium dodecyl sulfate: cocamidopropyl betaine: sodium fatty alcohol polyoxyethylene ether sulfate: sodium dodecylbenzene sulfonate in a weight ratio of (1-2):1:1:

1.

6. The composite automobile surface pretreatment liquid according to claim 1, characterized in that: The dispersant is prepared by mixing sodium polyacrylate: polyvinyl pyrrolidone: sodium carboxymethyl cellulose in a weight ratio of (2-3):2:

1.

7. The composite automobile surface pretreatment liquid according to claim 1, characterized in that: The pH regulator is prepared from citric acid: sodium hydroxide: sodium hydrogen phosphate in a weight ratio of (1-2): 1:

1.

8. A method for preparing the nano-silane-zirconium composite automobile surface pretreatment liquid as claimed in claim 1, characterized in that: The method comprises the following steps: ① Take 30 to 45 parts of deionized water, heat it to 40°C to 50°C, then add the surfactant and continue stirring for 15 to 30 minutes at a stirring speed of 300 to 500 rpm to form a surfactant solution; ② Take 5 to 10 parts of deionized water, heat it to 50°C to 60°C, then add the dispersant and continue stirring for 15 to 30 minutes at a stirring speed of 400 to 600 rpm to form a dispersant solution; ③ According to the compounding ratio, citric acid, sodium hydroxide and sodium hydrogen phosphate are added to 5-10 parts of deionized water, stirred at a speed of 400-600 rpm for 15-30 minutes to prepare a pH regulator solution; ④ Mix zirconium nitrate and zirconium chloride in a weight ratio of (1-2):2 to prepare the required zirconium salt; ⑤ Adjust the stirring speed of the high-speed stirrer to 1300-1500 rpm, add the nanoparticles, stir for 15-30 minutes, then add the silane coupling agent and zirconium salt, and continue stirring for 15-30 minutes; ⑥ Add the surfactant solution obtained in step ①, the dispersant solution obtained in step ②, the pH regulator solution obtained in step ③, and the remaining deionized water into the high-speed stirrer, control the stirring speed to 2000-3000 rpm, the stirring temperature to 60° C.-75° C., and the stirring time to 45-60 minutes to obtain a nano-silane-zirconium composite automobile surface pretreatment liquid.

Citation Information

Patent Citations

  • Nano-silicon ceramic compound treating liquid and preparation method thereof

    CN106148930A

  • Compound chromate-free passivator capable of forming films rapidly and preparation method

    CN108300988A

  • Metal surface multifunctional environment-friendly type nanometer ceramization liquid and preparing method and using method thereof

    CN109321908A

  • Silane vitrifying agent for metal surface pretreatment as well as preparation method and use method thereof

    CN112111732A

  • Preparation method of environmental-friendly nano-filming agent

    CN112921312A